Science Literacy Ability of Elementary Students Through Nature of Science-based Learning with the Utilization of the Ministry of Education and Culture's "Learning House" - Hana Lestari; Wawan Setiawan; Ridwan Siskandar (Jurnal Penelitian Pendidikan IPA, 2020)
Students' scientific literacy skills can be developed and enhanced with appropriate learning models and supported by adequate technology. This study aims to determine the improvement of the science literacy skills of elementary students through the Nature of Science learning model by utilizing the "Learning house" feature of the Ministry of Education and Culture. The research method used was a pre-experiment with one group pretest-posttest design. The instrument used was in the form of a science literacy ability test and an observation sheet of learning implementation with the research subjects of 38 students of Cibatok I Elementary School, Bogor, West Java, VA, and VB classes in 2018/2019 school year. The data obtained were analyzed by the Wilcoxon test using SPSS 22 at α (0.05). The results showed that (1) there was an increase in students' scientific literacy skills through the Nature of Science learning model by utilizing the "Learning house" feature of the Ministry of Education and Culture, this was indicated by sig (0,000) <α (0.05); (2) The average scientific literacy ability of students after being given the Nature of Science learning model by utilizing the "Learning house" feature of the Ministry of Education and Culture (3.75) is higher than the average scientific literacy ability of students before being given the Nature of Science learning model by utilizing the Ministry of Education and Culture's "Learning house" feature (2.57). It can be concluded that the Nature of Science learning model by utilizing the " Learning house" feature of the Ministry of Education and Culture can significantly increase the level of students' scientific literacy abilities.